Analysis of the Potential of BRICS Currencies in Challenging the Dominance of the US Dollar in the Perspective of Islamic Monetary Economics: Advantages and Challenges - Ahmad Ramadhan; Hasibuan, Syarinah Junianti (Business Finence Analyst Co.,, 2024)
This research aims to analyze the potential of the BRICS currency in challenging the dominance of the US dollar from the perspective of Islamic monetary economics. The study examines the advantages and challenges associated with the emergence of the BRICS currency as an alternative to the US dollar in international trade and finance, focusing on the principles of Islamic monetary economics, which emphasize justice, stability, and sustainability. A qualitative method is used in this research, with data sourced from journals, books, and articles. The main analytical tools are exchange rates and foreign policy. The research findings indicate that the potential emergence of the BRICS currency is driven by longstanding dependence on the hegemony of the US dollar, which benefits the US more than developing countries. However, the BRICS currency is deemed less potential due to the need for substantial financial infrastructure and competition with the World Bank. Therefore, BRICS should consider an Islamic financial system based on principles of justice, sustainability, and economic independence.